Aripana Art of Mithila Culture in Nepal: A Study of Symbols and Significance - Dulal, Lok Nath; K. C., Raju; Singh, Ankita (International Journal of Culture and History, 2023)
Nepal is a small and landlocked but richest country in diverse natural and cultural resources that are considered our heritage. Not only status and glory, but the unique identity of our nation is also represented by the temples, monasteries, images, different art forms, feasts, festivals, the mountains, rivers, forests, lakes as well as various beautiful places. Rest of the different art forms, Aripana is an important cultural heritage of Mithila region in Nepal. It is a floor painting painted especially on the court yard of the houses and other buildings in Mithila region, hence it is known as an amazing art heritage of Maithili culture. Mithila region and Maithili culture has advanced tradition of creating different forms of art both in religious and secular motifs. Among them as the floor painting Aripana is considered beautiful creation through the perspective of cultural heritage of not only in Mithila region but entire the nation. Although it is still not properly recognized among the scholars and researchers as the maters of study and research, hence, several aspects of Aripana painting is still remained under research. It is its research gaps and research problems as well. Therefore, for addressing the gaps and problems this paper has been prepared. The main aim of this paper is to explore and highlight the concept of Aripana painting, history and practices, creating methods and materials, types and typology, symbol and significant of such type of cultural heritage of Mithila region and Nepal as well.